A medieval fallacy: the crystalline lens in the center of the eye - Leffler CT (Dove Medical Press, 2016)
Christopher T Leffler,1 Tamer M Hadi,2 Akrithi Udupa,1 Stephen G Schwartz,3 Daniel Schwartz1 1Department of Ophthalmology, Virginia Commonwealth University, Richmond, VA, 2Graduate School of Medicine, University of Tennessee Medical Center, Knoxville, TN, 3Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USA Objective: To determine whether, as most modern historians have written, ancient Greco-Roman authors believed the crystalline lens is positioned in the center of the eye. Background: Historians have written that statements about cataract couching by Celsus, or perhaps Galen of Pergamon, suggested a centrally located lens. Celsus specifically wrote that a couching needle placed intermediate between the corneal limbus and the lateral canthus enters an empty space, presumed to represent the posterior chamber. Methods: Ancient ophthalmic literature was analyzed to understand where these authors believed the crystalline lens was positioned. In order to estimate where Celsus proposed entering the eye during couching, we prospectively measured the distance from the temporal corneal limbus to the lateral canthus in 30 healthy adults. Results: Rufus of Ephesus and Galen wrote that the lens is anterior enough to contact the iris. Galen wrote that the lens equator joins other ocular structures at the corneoscleral junction. In 30 subjects, half the distance from the temporal corneal limbus to the lateral canthus was a mean of 4.5 mm (range: 3.3–5.3 mm). Descriptions of couching by Celsus and others are consistent with pars plana entry of the couching needle. Anterior angulation of the needle would permit contact of the needle with the lens. Conclusion: Ancient descriptions of anatomy and couching do not establish the microanatomic relationships of the ciliary region with any modern degree of accuracy. Nonetheless, ancient authors, such as Galen and Rufus, clearly understood that the lens is located anteriorly. There is little reason to believe that Celsus or other ancient authors held a variant understanding of the anatomy of a healthy eye. The notion of the central location of the lens seems to have arisen with Arabic authors in 9th century Mesopotamia, and lasted for over 7 centuries. Keywords: anatomy, medical history, crystalline lens, cataract couching